(untitled) (Journal of Universal Science Research, 2025)
English for Specific Purposes (ESP) has never been more important in training military cadets in a globalized military setting. In order to command operations, make decisions, and work with multinational forces, military personnel now need to be able to communicate effectively, which goes beyond simple language proficiency. This essay examines the value of communication competence in military cadet ESP training, highlighting its complexity, contribution to operational efficacy, and the difficulties teachers encounter in imparting it. The essay offers suggestions for improving language training in military contexts with the goal of raising cadets’ general communication effectiveness in demanding, multicultural settings.